Pengaruh Kepercayaan dan Persepsi Harga Terhadap Keputusan Pembelian Jasa GoRide (Studi Pada Mahasiswa Fakultas Ekonomi) Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Banjarmasin - Apriya Santi; Siti Mardah (Jurnal Ilmu Ekonomi dan Bisnis, 2021)
Abstract: The purposes of this study are to find out the effect of trust on purchase decision, knowing the effect of price perception on purchase decision and the effect of trust and price perception simultaneously on purchase decision. With a purposive sampling technique,there are 91 students as respondents. The analysis technique used to test the hypothesis is multiple linear regression. The results showed that the trust has significant effect on purchase decision, the price perception has significant effect on purchase decision, the trust and price simultaneously have significant effect on purchase decision of students in the Economic Faculty of the Islamic University of Kalimantan. Keywords : Trust, Price Perceptions, Purchase Decision